The Relation Between Thermodynamic and Structural Properties and Cellular Uptake of Peptides Containing Tryptophan and Arginine - Shirani, Ali (Adv Pharm Bull, 2015)
Purpose: Cell-penetrating peptides (CPPs) are used for delivering drugs and other macromolecular cargo into living cells. In this paper, we investigated the relationship between the structural/physicochemical properties of four new synthetic peptides containing arginine-tryptophan in terms of their cell membrane penetration efficiency. Methods: The peptides were prepared using solid phase synthesis procedure using FMOC protected amino acids. Fluorescence-activated cell sorting and ﬂuorescence imaging were used to evaluate uptake efficiency. Prediction of the peptide secondary structure and estimation of physicochemical properties was performed using the GOR V method and MPEx 3.2 software (Wimley-White scale, helical wheel projection and total hydrophobic moment). Results: Our data showed that the uptake eﬃciency of peptides with two tryptophans at the C- and N-terminus were significantly higher (about 4-fold) than that of peptides containing three tryptophans at both ends. The distribution of arginine at both ends also increased the uptake eﬃciency 2.52- and 7.18-fold, compared with arginine distribution at the middle of peptides. Conclusion: According to the obtained results the value of transfer free energies of peptides from the aqueous phase to membrane bilayer could be a good predictor for the cellular uptake efficiency of CPPs.